2013
DOI: 10.1155/2013/315982
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability and Hemodynamic Change in the Superior Mesenteric Artery by Acupuncture Stimulation of Lower Limb Points: A Randomized Crossover Trial

Abstract: Objective. We investigated the relationship between superior mesenteric artery blood flow volume (SMA BFV) and autonomic nerve activity in acupuncture stimulation of lower limb points through heart rate variability (HRV) evaluations. Methods. Twenty-six healthy volunteers underwent crossover applications of bilateral manual acupuncture stimulation at ST36 or LR3 or no stimulation. Heart rate, blood pressure, cardiac index, systemic vascular resistance index, SMA BFV, and HRV at rest and 30 min after the interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…This is consistent with the previous clinical observations of Huang et al 19 and Wang et al 20 We also found that the VLF component of HRV, which is believed to reflect the activity of the sympathetic nervous system, 3 was significantly higher in the HT7 verum acupuncture group than in the HT7 nonpenetrating sham acupuncture and no acupuncture groups, but not than the sham acupuncture point group. Similar results have been reported by Kaneko et al, 21 Zhang 22 and Chang et al 23 The mechanism by which acupuncture increases VLF remains undetermined. The pertinent difference between the sham acupuncture point and no acupuncture groups is that the needle of the former group penetrated the skin, as was also the case in the HT7 verum acupuncture group.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with the previous clinical observations of Huang et al 19 and Wang et al 20 We also found that the VLF component of HRV, which is believed to reflect the activity of the sympathetic nervous system, 3 was significantly higher in the HT7 verum acupuncture group than in the HT7 nonpenetrating sham acupuncture and no acupuncture groups, but not than the sham acupuncture point group. Similar results have been reported by Kaneko et al, 21 Zhang 22 and Chang et al 23 The mechanism by which acupuncture increases VLF remains undetermined. The pertinent difference between the sham acupuncture point and no acupuncture groups is that the needle of the former group penetrated the skin, as was also the case in the HT7 verum acupuncture group.…”
Section: Discussionsupporting
confidence: 87%
“…The exclusion criteria were: (1) undergoing chemotherapy or radiotherapy for therapeutic purposes; (2) having undergone past acupressure therapy of the Neiguan and the Zusanli (Fig. 1) (Kaneko et al 2013;Shimizu and Miyashita 2016); (3) meeting Palliative Performance Scale (PPS) (Anderson et al 1996) score between 10 and 20; (4) having a medical history of bradycardia arrhythmias such as sick sinus syndrome, atrioventricular block or bradycardiac atrial fi brillation; (5) having mental symptoms such as delirium; or (6) being considered unsuitable for the study by the researcher (for example, due to edema at the acupressure site).…”
Section: Participants and Settingmentioning
confidence: 99%
“…Although Kaneko et al reported that Taichong acupuncture (LR3) did not lower BP in their study patients [ 12 ], other studies in both animals and humans have suggested that acupuncture on the Taichong acupoint is effective in the treatment of hypertension [ 13 – 21 ]. The effect of acupuncture on the Taichong acupoint in the treatment of hypertension is rapid in onset, lowering systolic and diastolic BP within 20–30 min [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%